CHARISMATIC LEADERSHIP IN BENGKULU CITY HARSALLAKUM AL-QURAN ISLAMIC BOARDING SCHOOL - Mulyadi, Mus (Journal of Education Research in Administration and Management (JERAM), 2017)
Charismatic leadership involves determination, authority, openness, and the optimism of the leaders in Bengkulu City Harsallakum Pesantern (Pesantren = Islamic Boarding School). This research uses descriptive method, as well as qualitative case study. The processing of data is done by data reduction, serving of the next, as well as doing the valid checking using triangulation technic, followed by concluding the findings. The result of the research, has swon that the leadership of Pesantren leaders has been a model for the people around. Being an example or a role model has created a harmonic relationship between Santri (cultural 'stream' of people within the population of Javanese who practice a more orthodox version of Islam) with the Usthad (Islamic leader). The prestige of the Pesantren leaders has created an awareness for their subordinates, that to accept, prestige has to rise from the bottom going upwards. The openness of the Pesantren leaders acts truthfully, humble, just, as well as open in accepting opinions and critics from others. The openness of Pesantren leader shows the clearliness in taking decisions, planning process that gives a chance to all subordinates. Optimism of the Pesantren leaders are behaviors that is born or created inside of the leaders in perceiving their problem, facing hardship, and thinking optimistic. So that the biggest strength is giving enery and directions in reaching the destination.